Groundwater Model Simulations of Stakeholder‐Identified Scenarios in a High‐Conflict Irrigated Area. Issue 6 (1st March 2020) - Kniffin, Maribeth; Bradbury, Kenneth R.; Fienen, Michael; Genskow, Kenneth
Abstract: This study investigated collaborative groundwater‐flow modeling and scenario analysis in the Little Plover River basin, Wisconsin, USA where an unconfined aquifer supplies groundwater for agricultural irrigation, industrial processing, municipal water supply, and stream baseflow. We recruited stakeholders with diverse interests to identify, prioritize, and evaluate scenarios defined as management changes to the landscape. Using a groundwater flow model, we simulated the top 10 stakeholder‐ranked scenarios under historically informed dry, average, and wet weather conditions and evaluated the ability of scenarios to meet government‐defined stream flow performance measures. Results show that multiple changes to the landscape are necessary to maintain optimum stream flow, particularly during dry years. Yet, when landscape changes from three scenarios—transferring water from the local waste water treatment plant to basin headwaters, moving municipal wells further from the river and downstream, and converting 240 acre (97 ha) of irrigated land to unirrigated land—were simulated in combination, the probability of meeting or exceeding optimum flows rose to 75, 65, and 34% at upper, mid, and lower stream gages, respectively, in dry climate conditions. Discussions with stakeholders reveal that the collaborative model and scenario analysis process resulted in social learning that built upon the existing complex and dynamic institutional landscape. The approach provided a forum for solution‐based discussions, and the model served as an important mediation tool for the development and evaluation of community‐defined scenarios in a high conflict environment. Today, stakeholders continue to work collaboratively to overcome challenges and implement voluntary solutions in the basin. Abstract : Article impact statement : Collaborative groundwater flow model simulations of stakeholder‐developed scenarios aided in the development of water resources solutions.